Singing Methods in Improving Personal Hygiene Independence in School-Age Children - Hera Hijriani; Aat Agustini; Idris Handriana; Wawan Kurniawan; Je'an Zeina Fahira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to understand the effect of the singing method on independence in the personal hygiene of school-age children in Leuwikidang Village, Majalengka Regency, in 2022. The technique used is a quantitative and cross-sectional approach using a purposive sampling technique. The results showed that the percentage of independence in personal hygiene for children was carried out before carrying out health education using the singing method (53.3%) and after carrying out health education using the singing method (60.0%). In conclusion, there is a significant influence on the personal hygiene independence of school-age children in Leuwikidang Village with health education and the singing method. Keywords: School Age Children, Personal Hygiene Independence, Singing Method